The early modern subject self-consciousness and personal identity from Descartes to Hume - Thiel, Udo, 1954- (Oxford : Oxford University Press, 2011)
Udo Thiel presents a critical evaluation of the understanding of self-consciousness and personal identity in early modern philosophy. He explores over a century of philosophical debate from Descartes to Hume, and argues that our interest in human subjectivity remains influenced by the conceptual framework of early modern thought.
Also issued in print format.
Description based on online resource; title from PDF title page (viewed on Jan. 17, 2012).
Includes bibliographical references and index.
Keywords: Identity (Philosophical concept) -- History; Self-consciousness (Awareness) -- History; Philosophy, European -- 17th century; Philosophy, European -- 18th century